Manajemen Kepala Sekolah Dalam Mendukung Pelaksanaan Program Adiwiyata - Yuli Sudarti; Yasir Arafat; Nurlina Nurlina (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
This study aimed to obtain comprehensive information regarding the management of the Adiwiyata school at SMP Negeri 5 Prabumulih. This research uses a qualitative approach with descriptive methods. Information in this study was obtained from sources of school principals, teachers, and students. Data collection procedures were carried out by observation, structured and in-depth interviews, and documentation. Checking the validity of the findings is carried out by carrying out reference adequacy and triangulation. Data analysis used is qualitative analysis, namely by describing and interpreting the data. The results of this study are that the process of planning, implementing, and evaluating the Adiwiyata school at SMP Negeri 5 Prabumulih has gone well. In conclusion, the fundamental difference from this study lies in the object of research related to the Adiwiyata program, especially at the junior high school (SMP) level. Keywords: Adiwiyata, Principal, Management, Management